Gendered Returns, Ambivalent Transnationals: Situating Transnationalism in Local Asymmetry: Graduate Student Papers in Feminist Anthropology Award - Bryan, Catherine (Anthropologica, 2022)
Drawing on interviews with migrants to Halifax, Nova Scotia, this article illustrates the potential discrepancy between the aspirations of even the most affluent global migrants and the local contexts of immigration. Attracted to Canada for its pluralism, participants sought to contribute to Canadian society while ensuring new opportunities for female family members. However, faced with unemployment, participants developed transnational strategies that reinforced normative gender roles. Furthermore, these strategies engendered a kind of ambiva lent transnationalism whereby participants wished to establish themselves locally but, due to conditions in the site of immi gration, were compelled to remain highly connected to their countries of origin.